Alternative underground ore transport systems for the Jaguar Base Metal deposit - Darcey, W.; Chanda, E.; Kuruppu, Mahinda (2011)
Jabiru Metals completed a feasibility study on the Jaguar Base Metal Project in July 2005. The study was based on conventional truck haulage via a decline. Conveyor haulage was considered but not in sufficient detail to provide a meaningful comparison. The current study investigates the cost and productivity of alternative ore transport systems for the Jaguar project. The options considered are conventional underground truck, conveyor, road train, rigid frame truck, monorail haulage and shaft hoisting. Shaft hoisting was not considered in detail due to the high capital outlay for such a relatively short mine life of less than six years. This study goes beyond the common approach of evaluating haulage systems in isolation; it includes development costs, timing of ore production and costs associated with mine services as well as administration and milling costs. The results of this study indicate that the best haulage option for the Jaguar project is conventional truck using the Hitachi AH400 trucks. The net present value (NPV) for this option is A$8.13 million higher than the next best option namely the Kiruna E635 electric truck. The conveyor option has the lowest operating cost per tonne of ore but the longer development time negatively impacts on its NPV. The monorail option is considered impractical due to the number and length of trains required to achieve production targets.